Pengaruh Warna Terhadap Short Term Memory Pada Anggota UKM Creative Minority - Nurjannah Nasution; Putri Ratna Sari; Satrian Sastra (Jurnal Psikologi Terapan, 2019)
The purpose of this study was to determine the effect of color on short term memory among student members of the Creative minority UKM, Malikussaleh University. The hypothesis in this study is the effect of color on short term memory, where students who are given colored paper with animal names written on it have better short-term memory than those who are not given colored paper. The study was conducted on 30 creative minority UKM members aged 18-22 years consisting of two groups, namely the control group and the experimental group, each of which was 15 respondents using a randomized two group design experiment - post test only. The independent sample t test results indicate that there is an influence between color on short term memory in creative minority UKM members. The conclusion of this study is that color has an effect on increasing achievement motivation. The next researcher is expected to be able to increase the number of respondents and control the situations and conditions during the experiment and be able to try researching new colors.